Comparação de espaçamentos entre estacas e métodos de cálculos na sistematização de terrenos para irrigação - Tuler , José Cláudio; Bernardo , Salassier; Vieira , Manoel; Sediyama, Gilberto C (Revista Ceres, 2025)
A study was made of the effect of land grading computation methods and staking intervals on the calculated volumes of cutting and land filling. Methods compared were the least square method, method of moments, the unique plane method and the centroid method.